Ownership structure impacting value relevance of accounting information - Shamki, Dhiaa; Al-Arussi, Ali (IJERMT All Rights Reserved, 2015)
The paper aims to indicate the impact of ownership structure traced by domestic and foreign shareholders numbers on the value relevance of earnings and book value individually and in aggregate for Jordanian industrial sector within the period from 1992 to 2002.Using price model, domestic and total shareholders numbers significantly declined the value relevance of both individual and aggregate book value but not that of earnings. Foreign shareholders number shows no impact on the value relevance of both accounting variables.Domestic and total shareholders numbers affected more the value relevance of book value than that of earnings.In their combination, share price responds more to book value than earnings when the impact of ownership structure is included.Our findings might provide financial reporting users with a good comprehension regarding the valuation practices and set prime fundamentals for future research that is interested in testing our hypotheses in more details.